Pemanfaatan Posyandu Guna Meningkatkan Kesehatan Lansia di Pedukuhan Sarigono Desa Pagerharjo - Titis Ratna Djuwita; Rizfa Fadilah (Yayasan REDI Tiga Monas, 2024)
Elderly people generally experience various degenerative diseases due to decreased biological, psychological, social and economic functions. A decrease in these various functions will have an impact on aspects, especially health. Therefore, this community service activity aims to improve the health of the elderly through the use of posyandu in Sarigono Hamlet, Pagerharjo Village. This activity provides benefits to the elderly in Sarigono Hamlet, Pagerharjo Village, namely as a preventive means of checking disease and health in the elderly.